DEVELOPMENT OF ELECTRONIC ARCHIVES MANAGEMENT LEARNING MEDIA (E-ARCHIVING) USING THE MICROSOFT ACCESS APPLICATION FOR STUDENTS OF SMKN 40 JAKARTA - Putri Aisyah Salsabil; Marsofiyati; Nadya Fadillah F (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to develop an Electronic Archives Management (E-Archive) learning media using Microsoft Access for students at SMKN 40 Jakarta. The method used is Research and Development with a 4D development model (Define, Design, Develop, and Disseminate), although this study was limited to the first three stages due to time constraints. The product developed is a digital learning module integrated with Microsoft Access, designed to enhance students' understanding of archiving practices in the digital era. Validation results from material, design, and media experts yielded an average score of 91%, categorized as